Targeting the gut to heal the skin: probiotic supplementation reduces wound infection risk and clinical burden in critically ill patients—a systematic review and meta-analysis - Peng, Yu; Yan, Hao; Shi, Bowen; Lv, Lingyun; Jiang, Yu; Fang, He; Ma, Bing (Frontiers in Nutrition, 2026)
ObjectiveTo systematically evaluate the impact of probiotic supplementation on wound-specific and systemic clinical outcomes in critically ill patients.MethodsWe conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) according to PRISMA guidelines. A comprehensive search of six databases was performed up to December 31, 2025. We included RCTs of probiotic/synbiotic interventions in adult ICU patients reporting wound-related outcomes. Study quality and evidence certainty were assessed using Cochrane RoB 2.0 and GRADE frameworks. Data were pooled using random-effects models.ResultsNineteen RCTs involving 1,384 patients were included. Probiotic supplementation significantly reduced the risk of wound infection (RR = 0.52, 95% CI: 0.38–0.71), with the most pronounced benefit observed in burn patients. It also significantly reduced hospital length of stay (MD = −5.24 days, 95% CI: −8.73 to −1.75) and the duration of antibiotic use (SMD = −0.18, 95% CI: −0.25 to −0.11), and the duration of mechanical ventilation (SMD = −0.90, 95% CI: −1.20 to −0.60). Probiotics were associated with reduced systemic inflammation (CRP SMD = −0.73, 95% CI: −1.15 to −0.32) and improved intestinal barrier function (RR = 1.63, 95% CI: 1.28–2.08). However, no significant effect was found on wound healing time (MD = −5.60 days, 95% CI: −23.09 to 11.88). While overall mortality was not significantly reduced (RR = 0.75, 95% CI: 0.56–1.01, p = 0.06), a significant benefit was observed in severely ill patients (APACHE II > 20). Sensitivity analyses confirmed the robustness of the primary findings.ConclusionModerate-certainty evidence indicates that probiotic supplementation may serve as a beneficial adjunct in critical care, primarily for preventing wound infections and reducing hospital stay and mechanical ventilation duration, with particular efficacy in burn patients. Its effect on accelerating wound healing remains inconclusive. Future research should focus on standardizing interventions and evaluating long-term outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251276093, identifier CRD420251276093.